Effect of Peri-natal Supplementation of Amino acids on Post-hatch Performance of Broiler Chicken - Saravanakumar, M. (Indian Journal of Animal Nutrition, 2021)
An experiment was conducted to assess the effect of peri-natal supplementation of amino acids in broiler chicken. Three hundred and eighty Cobb broiler eggs set for incubation, were divided into un-supplemented and in ovo supplemented (lysine, methionine, arginine, threonine, and glutamine at 2.2, 1, 2.5, 1.6 and 2.5 mg/egg) groups on 18 days of incubation. Following hatching, un-supplemented group was again sub-divided into un-supplemented (control) and post-hatch supplemented group. The post hatch supplemented diet consisted of 25 % extra amino acids (lysine, methionine, threonine, arginine, glutamine) than that in starter diet for first 3 days. Results indicated poor hatchability of fertile eggs on in ovo supplementation. The body weight gain, feed intake and feed conversion ratio did not differ significantly (P>0.05) among treatments. At first week of age, longer (P<0.008) length of jejunal villus was observed in post-hatch amino acid supplemented group (161 µm) as compared to in ovo supplemented (93.5 µm) and control (117 µm) groups. Humoral immune response was better (P < 0.013) in broiler chicks on in ovo and post-hatch supplementation. The ileal digestibility coefficient of crude protein, calcium and phosphorus were not influenced (P>0.05) by in ovo and post-hatch supplementation of amino acids. It could be concluded that in ovo supplementation of (lysine, methionine, arginine, threonine, and glutamine at 2.2, 1, 2.5, 1.6 and 2.5 mg/egg) or post-hatch supplementation of 25 % extra amino acids (lysine, methionine, threonine, arginine, glutamine) did not influence the growth performances of broiler chicken. However, humoral immune response was better on in ovo and post-hatch supplementation.